Concrete as low-cost catalyst to improve gas quality during biomass gasification in a pilot-scale gasifier. (15th October 2021) - Pio, D.T.; Gomes, H.G.M.F.; Ruivo, L.C.M.; Matos, M.A.A.; Monteiro, J.F.; Frade, J.R.; Tarelho, L.A.C.
Abstract: Concrete was evaluated as low-cost catalyst for in-situ application in an autothermal 80 kWth pilot-scale bubbling fluidized bed direct (air) biomass gasifier. To improve the understanding of the observed phenomena, the process was also evaluated in smaller-scale reactive system, namely an externally heated 3 kWth bench-scale bubbling fluidized bed. Concrete application showed promising results regarding the relative increase of H2 concentration and H2 /CO molar ratio in the producer gas (up to 99.2 and 77.4%, respectively), indicating that this material can promote the water-gas shift reaction. However, this effect was dependent on the gas-solid contact time and catalyst temperature, being that it was only relevant when these parameters were at least 5.2 s and 746 °C, respectively. A maximum lower heating value of 7.5 MJ/Nm 3 of the producer gas was found with concrete application (23.8% relative increase), which is higher than commonly found in the literature. Relative increases of up to 25.1, 55.3 and 47.0% for the specific dry gas production, cold gas efficiency and carbon conversion efficiency, respectively, were also found, consequently suggesting that, in addition to the promotion of the water-gas shift reaction, this material has potential to promote tar reforming/cracking and carbon gasification reactions. Highlights: Concrete as catalyst in biomass gasification in a pilot-scale BFB reactor. Concrete promotes increased H2 concentration and H2 /CO ratio in the producer gas. Concrete promotes higher gas yield and cold gas and carbon conversion efficiencies. Concrete promotes tar reforming/cracking and carbon gasification reactions.